Effect of the low energy ion bombardment on the optical properties of metallic mirrors - Bandourko, V.; Kishimoto, N.; Kurnaev, V.A.; Nakamura, K.; Sugie, T.; Voitsenya, V.S. (Вопросы атомной науки и техники, 2000)
Schemes of several methods of plasma diagnostics in ITER in a high degree must be based on utilization of the reflective optics. In this connection there appeared the problem of the first mirrors (FM), i.e., mirrors directed to plasma under investigation. The FMs will be subjected to bombardment by charge exchange atoms (CXA) and to deposition of contaminating materials. The CXA energy distribution will be very different for different mirrors, namely, it will be much higher with long tail in the case of mirrors for the core plasma than for mirrors in the divertor region. In this paper we present some results of investigations of effect of the long-term bombardment by deuterium ions with sub- or near-threshold energy on reflectance of metallic mirrors.